PSIKOEDUKASI BERBASIS SEKOLAH UNTUK MENINGKATKAN LITERASI KESEHATAN MENTAL GURU DALAM PENCEGAHAN MASALAH KESEHATAN MENTAL REMAJA - Wahyi Suswati (LPPM Universitas dr. Soebandi, 2024)
Schools are the right place for interventions to promote and prevent mental health problems for adolescents, especially by teachers. Therefore, teacher literacy regarding the mental health of adolescent students needs to be increased through school-based psychoeducation. The aim of this activity is helping teachers to recognize, prevent and help teenage students who have mental health problems at school. The method of implementing activities starts from the preparation, implementation and evaluation. Preparation consists of licensing the time and place for carrying out activities, material preparation, and other logistical tools. The implementation of psychoeducation is divided into 3 sessions: material delivery; discussion; and sharing session. Evaluation is carried out by filling out a mental health knowledge test at the beginning and end of the activity. The result obtained an increase in the average value of mental health literacy in teachers before and after being given psychoeducation from 68 points to 81 points. School-based psychoeducation has the benefit of increasing teachers' mental health literacy about adolescent students so that teachers' abilities to recognize, identify and deal with mental health problems of adolescent students become better in order to minimize the need for interventions for mental health problems in the future.